Circulatory Immune Cells in Cushing Syndrome: Bystanders or Active Contributors to Atherometabolic Injury? A Study of Adhesion and Activation of Cell Surface Markers - Gloria Aranda; Cristina Lopez; Rebeca Fernandez-Ruiz; Yaiza Esteban; Guillermo Garcia-Eguren; Mireia Mora; Irene Halperin; Gregori Casals; Joaquim Enseñat; Felicia A. Hanzu (International Journal of Endocrinology)
Glucocorticoids (GC) induce cardiometabolic risk while atherosclerosis is a chronic inflammation involving immunity. GC are immune suppressors, and the adrenocorticotrophic hormone (ACTH) has immune modulator activities. Both may act in atherothrombotic inflammation involving immune cells (IMNC). Aim. To investigate adhesion and activation surface cell markers (CDs) of peripheral IMNC in endogenous Cushing syndrome (CS) and the immune modulator role of ACTH. Material and Methods. 16 ACTH-dependent CS (ACTH-D), 10 ACTH-independent (ACTH-ID) CS, and 16 healthy controls (C) were included. Leukocytes (Leuc), monocytes (MN), lymphocytes (Lym), and neutrophils (N) were analyzed by flow cytometry for atherosclerosis previously associated with CDs. Results. Leuc, N, and MN correlated with CS (p<0.05), WC (p<0.001), WHR (p=0.003), BMI (p<0.001), and hs-CRP (p<0.001). CD14++CD16+ (p=0.047); CD14+CD16++ (p=0.053) MN; CD15+ (p=0.027); CD15+CD16+ (p=0.008) N; and NK-Lym (p=0.019) were higher in CS. CD14+CD16++ MN were higher in ACTH-ID (8.9 ± 3.5%) versus ACTH-D CS (4.2 ± 1.9%) versus C (4.9 ± 2.3%). NK-Lym correlated with c-LDL (r = 0.433, p=0.039) and CD15+ N with hs-CRP (r = 0.446, p=0.037). In multivariate analysis, Leuc, N, and MN depended on BMI (p=0.021), WC (p=0.002), and WHR (p=0.014), while CD15+ and CD15+CD16+ N on hypercortisolism and CS (p=0.035). Conclusion. In CS, IMNC present changes in activation and adhesion CDs implicated in atherothrombotic inflammation. ACTH-IDCS presents a particular IMNC phenotype, possibly due to the absence of the immune modulator effect of ACTH.